1997
DOI: 10.1046/j.1469-0705.1997.09010039.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the fetal tongue between 14 and 26 weeks of gestation: in utero ultrasonographic measurements

Abstract: Our objective was to establish nomograms for fetal tongue measurements from 14 weeks until mid-gestation by using transvaginal and transabdominal high-resolution ultrasound techniques. A prospective, cross-sectional study was performed on 120 normal singleton pregnancies between 14 and 26 weeks of gestation. Tongue circumference was measured by transvaginal ultrasonography between 14 and 17 weeks, and by abdominal ultrasound between 18 and 26 weeks of gestation. Fetal tongue circumference, as a function of ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…A linear relationship between lingual width and gestational age was demonstrated. Very recently Achiron et al (1997) found a linear relationship between lingual circumference and gestational age. However, because the proximal border of the tongue cannot accurately be determined we believe measurements of the lingual width are more reliable compared with measurements of the lingual length or circumference.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A linear relationship between lingual width and gestational age was demonstrated. Very recently Achiron et al (1997) found a linear relationship between lingual circumference and gestational age. However, because the proximal border of the tongue cannot accurately be determined we believe measurements of the lingual width are more reliable compared with measurements of the lingual length or circumference.…”
Section: Discussionmentioning
confidence: 95%
“…However, because the proximal border of the tongue cannot accurately be determined we believe measurements of the lingual width are more reliable compared with measurements of the lingual length or circumference. In the study of Achiron et al (1997) two abnormal fetuses were evaluated at 24 weeks' gestation. One fetus with trisomy 21 had macroglossia, and the second with partial trisomy 1 had microglossia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have documented the development of oro-facial movements in the fetus (e.g., [1015]), including mouth opening which has been observed in the fetus at 7 to 8 weeks of gestation, sucking at 15 weeks, and swallowing of amniotic fluid at 12 to 14 weeks. Yan et al ([14]: page 112) defined sucking, observed in 6 out of 10 fetuses once or twice as “a series of movements of the jaws accompanied by the sinking of the cheeks toward the oral cavity, with the fingers always in the mouth.” This contrasts with our observations of the unobstructed fetal face which did not include any stimulation of the oral region.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al ([14]: page 112) defined sucking, observed in 6 out of 10 fetuses once or twice as “a series of movements of the jaws accompanied by the sinking of the cheeks toward the oral cavity, with the fingers always in the mouth.” This contrasts with our observations of the unobstructed fetal face which did not include any stimulation of the oral region. Additionally, some researchers have examined jaw and tongue movements (e.g., [15]). Mizuno and Udea [4] assessed sucking performance in premature infants weekly between 24 to 36 weeks postconceptual age and suggested that the normative data collected on healthy premature infants could serve as a measure to identify preterm infants with sucking difficulties.…”
Section: Introductionmentioning
confidence: 99%